NTPDase2+ Cells Generate Lingual Epithelia and Papillae - Feng, Li; Cao, Jie; Zhou, Mingliang (Frontiers in Genetics, 2012)
The tongue epithelium is one of the most rapidly self-renewing tissues in adult mammals. Multiple stem cell populations are currently believed to exist in tongue epithelia. Keratin 14 (K14) positive cells differentiate into either lingual epithelia or lingual papillae, while ecto-nucleoside triphosphate diphosphohydrolase 2 (NTPDase2) is associated with neural stem cells and astrocyte-like cells ensheathing the migrating neuroblasts. Here, using a transgenic mouse expressing rtTA from the mouse NTPDase2 promoter, we generated an inducible model by treatment with Doxycycline. By immunohistochemical analysis and in situ hybridization, we found exclusive expression of NTPDase2 in lingual epithelia and lingual papillae. Using inducible genetic cell fate mapping, we further showed that the NTPDase2+ cells generated lingual papillae and epithelia in the adult tongue. Finally, building on our previously proposed paradigm of cell migration stream, a model is further described here for lingual epithelia cell genesis. In short, the current results not only extend our understanding of the cell migration stream in lingual epithelia and lingual papillae, but they also support the concept of multiple stem cell populations in lingual epithelia and papillae.